Efeitos do treinamento de musculação em circuito sobre a aptidão cardiorrespiratória e citocinas plasmáticas IL-6, IL-8, IL-10, TNF, IL-1β e IL-12p70 em mulheres saudáveis - Nicioli, Cristiane (Universidade Federal de São Carlos, 2008)
There are evidences demonstrating that long-term aerobic exercises boost the plasmatic cytokines concentrations. However, there are few researches that deal with that relation in short-term and high intensity ones. This study aims at verifying the effects of strength training in circuit over the cardiorespiratory competence response and also over the plasmatic cytokines IL-6, IL-8, IL-10, IL-1β, IL-12p70 and TNF, by acute application of both tests, incremental and 35 minutes with Ventilatory Threshold (WVT) and maximum (IVO2peak) intensities. The research included 14 women, 40,23 (3,9) mean age, 164 (6,6) cm and 57,84 (7,7) kg. They did a single cycle exercise test with two stations, 30 minutes on WVT and 5 minutes on IVO2peak, just before and after strength training in circuit. The blood samples were taken at the rest time, immediately after the first and the second exercise stations for plasma cytokines analysis: interleukin 8 (IL-8), interleukin 10 (IL-10), interleukin 6 (IL-6), interleukin 12p70 (IL-12p70), interleukin 1β (IL-1 β) and tumoral necrosis factor (TNF). The cycle incremental test was conducted to verify the peak oxygen consumption (VO2peak) and the loads corresponding to the WVT and to the exhaustion. The analysis verified there are no changes in plasmatic cytokines when comparing the pre and post strength training in circuit, however, after the acute phase of the 5 minutes station in IVO2peak, there were increasing on IL- 6 during both pre [1,81 (1,36-5,05) vs. 3,09 (1,49-8,95) pg.mL-1; P=0,038] and post-training [1,62 (1,38-3,05) vs. 2,42 (1,46-5,71) pg.mL-1; P=0,021]. There were also improvement in the volunteer load [125 (100 150) vs. 150 (100-175) W; P=0,017] at the end of the intervention period. Hence, we conclude that the expression of IL-6 in plasma is protocoldependent and that the strength training in circuit does not trigger an inflammatory state, keeping the baseline concentrations of plasma cytokines unchanged. Keywords: Strength training in circuit. Cytokines. Acute phase. Ergometric cycle.
Keywords: Fisiologia do exercício físico; Citocina; Exercício resistido; Cicloergômetro; CIENCIAS BIOLOGICAS::FISIOLOGIA